An insight on the flora species and meiofauna distribution at Pantai Kelanang mangrove forest, Morib, Selangor - Maziah Mohd Ghazaly,; Maizah M. Abdullah,; Nur Sayyidah Afifah Mohd Radif,; Yusrina Safura Ghazali,; Siti Fatimah Tajuddin,; Nur Hidayah Ahmad Pauzi,; Razifah Mohd Razali, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Mangrove forest at Pantai Kelanang was famous for its diverse marine wildlife and various density of flora and meiofauna distributed at Morib shorelines. Moreover, the diverse marine wildlife, variation of flora and meiofauna distribution at Kelanang mangrove area has never been documented. Kelanang mangrove forest is also surrounded within heavy industrial activity zoning along the Malacca Straits. The objective of this study is to determine the diversity and distribution density of the mangrove flora and meiofauna at different intertidal zones influenced by prolonged human activities. Block sampling technique with quadrat analysis was used in this study. There are two major plants species belonging to Avicennia and Sonneratia families that have been discovered, where the average diameter at breast height was recorded between 3.3 to 32 cm and the average height ranged between 2.0 to 14.5 m. Whereas, Nematoda was found to be the largest distributed meiofauna compared to other meiofauna taxa such as Harpacticoida, Copepoda, Oligochaetea and Polychaetea. Flora species at Kelanang mangrove forest are less diverse at different intertidal zones and the meiofauna diversity were less at the mid- and high-intertidal zones. This finding may be a direct consequence of the influence of heavy industrial activities along the Malacca Straits.